The Importance of Copper Mineral in Animal Body Relating to Animal Disease - Arifin, Zainal (Indonesian Animal Sciences Society, 2007)
Copper is one of the micro elements that has very important roles in the process of body metabolism. Some enzymes are bound with copper and iron in the formation of blood haemoglobin. Copper deficiency in animal body will cause inappropriate function of the enzyme system, so that metabolism and physiological systems of the body will not work normally and if copper is in excess, it will cause toxicity which then destroys body tissues causes troubles in blood formation, Therefore, it is clear that copper has an important role in the process of living, hence monitoring its concentration in the blood is important to maintain animal health. Â Key words: Copper, deficiency, toxicity, health